The significant role of big data analytics in business: A review case study - Arumugam, Nalini; Bakri, Mohammed Hariri; Md Razak, Mohamad Idham; Mello, Geraldine De (Brooklyn Research and Publishing Institute, 2023)
It is noted that many organizations attempt to access getting access to records and available information via social media to heighten their performance overall performance and boom their returns. It is likewise noted that processing heterogeneous kinds of facts to retrieve poses a challenge to most companies which the leaders are striving to resolve them. As the Big Data trend has the competence to guide a radical transformation era in research, invention, and business marketing for Storing, Processing, and reading facts, corporations, appear to be the crucial trend. Organizations are managing data to use it at new ranges and direct decision-makers to make supple decisions in real time. This study spotlights a few components of Big Data, its significant roles in businesses` overall performance, and how corporations can use well-known organizations' business performance. In addition, the study also explains the ways organizations can benefit from the well-known established opensource platform Hadoop to method information to benefit the advanced competitive arena.